Measures and Metrics: exploring some of the philosophical roots of accountability regimes in higher education with a specific focus on the Irish context - SEERY, AIDAN (My University, 2012)
This paper reports on project aimed at examining the impact of accountability regimes on academic identity/identities in Ireland. Framed by a view of Foucaultian power relations and the Zizekian idea that academic life may contain irreducible fissures and voids that defy any totalizing descriptions, a number of extended interviews were carried out with academics in four of Ireland?s seven universities. An initial analysis of the defining tensions in the lives of three of the academics interviewed reveals the difficult negotiation of their identities on three levels framed by policy, discipline and institution. These tensions are characterized by a heightened sensitivity and awareness of power relations both within and external to the university and manifest themselves in some cases in variable modes of acceptance and resistance to the use of metrics - actual or anticipated. A second result of the analysis is that the Zizekian notion of an inherent disruptive ?excess? in the internal dialectic between metric and accountability systems and self is not [yet!] evident in the lives under consideration. However, the interpretative framework adopted is offered as a useful tool that reveals the tensions academics lives in a new light.
European Conference on Educational Research (ECER)
PUBLISHED
Cadiz
Keywords: higher education; accountability metrics; Identities in Transformation